The amendment and empirical test of arbitrage pricing models - Shaojun Wang; Xiaoping Yang; Juan Cheng; Yafang Zhang; Peibiao Zhao (Journal of Applied Finance & Banking, 2011)
The classical APT model is of the form rj - E(rj) = Øj (I - EI ) +ε , where rj - E(rj) is the earning deviation (called basic ariance-profit) of the security j, I is a common factor. This paper considers the impact on the securities return caused by the skewness and kurtosis of the stock returns distributions, and poses a re-modified the arbitrage pricing model as follows rj = E(rj ) + Øj (I - EI ) +j (I - EI )2 +λj (I - EI )3 +δj (I - EI )4 +ε Based on the regression analysis method, and the fitting degree, one can arrive at this re-modified model has a more reasonable explanation level for securities pricing.
Keywords: D46; E17; G11; G17; 330; arbitrage pricing models; skewness; Kurtosis; empirical analysis